Μετάφραση και Σχολιασμός των κειμένων: « Iran plays chess, the US plays backgammon», « Saudi Arabia and Iran, not places for persecuted religious and ethnic minorities», «Eastern Mediterranean: a microcosm of regional and global battles» από το blog του James M. Dorsey - (:unkn) unknown (My University, 2021)
Η παρούσα προπτυχιακή εργασία επικετρώνεται σε τρία άρθρα που γράφτηκαν από τον James M. Dorsey. Τα μεταφρασμένα άρθρα θεωρούνται σημείο αναφοράς για όσους επιθυμούν να ασχοληθούν με την ειδησησεογραφία της Μέσης Ανατολής και της Βόρειας Αφρικής. Η μετάφραση συνοδεύεται από μια ανάλυση, στην οποία αναφέρονται κάποιες γενικές παρατηρήσεις για το κείμενο και τα προβλήματα που αντιμετωπίστηκαν κατα τη μεταφραστική διαδικασία.

The present undergraduate thesis takes an interest in three articles written by James M. Dorsey. The articles translated have become a reference point for those who wish to engage and take part in the journalist world that includes issues having to deal with Middle East and North Africa. The translation is being accompanied by an analysis, in which the cultural connections, semantic, pragmatic and rhetorical aspects are thoroughly cited.
Keywords: Μετάφαρση, Σχολιασμός, Μέση Ανατολή; Translation, Commentary, Middle East